2019
DOI: 10.31234/osf.io/crzne
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Emotion recognition and deception detection

Abstract: People hold strong beliefs regarding the role of emotional cues in detecting deception. While research on the diagnostic value of such cues has been mixed, their influence on human veracity judgments should not be ignored. Here, we address the relationship between emotional information and veracity judgments. In Study 1, the role of emotion recognition in the process of detecting naturalistic lies was investigated. Decoders’ accuracy was compared based on differences in trait empathy and their ability to recog… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 67 publications
1
3
0
Order By: Relevance
“…There is little research on what could be called the “dark side of empathy.” The present study is consistent with a handful of others demonstrating downsides to extreme empathy (e.g., Longmire & Harrison, 2018; K. Scott, 2017; Simon et al, 2022; Zloteanu et al, 2019), but this literature is sparse. What is the difference between leaders who demonstrate “too much” empathy because of empathic distress compared to empathic concern?…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…There is little research on what could be called the “dark side of empathy.” The present study is consistent with a handful of others demonstrating downsides to extreme empathy (e.g., Longmire & Harrison, 2018; K. Scott, 2017; Simon et al, 2022; Zloteanu et al, 2019), but this literature is sparse. What is the difference between leaders who demonstrate “too much” empathy because of empathic distress compared to empathic concern?…”
Section: Discussionsupporting
confidence: 90%
“…There is little research on the possible overuse of empathy, but a few studies are suggestive. For instance, leaders who are very high in empathy can more easily be deceived by manipulative emotional cues (Zloteanu et al, 2019). Additionally, leaders who are prone to empathic distress and internalizing the suffering of others are more likely to do so to a debilitating extent that reduces their attention to other leadership requirements and overall effectiveness (Simon et al, 2022).…”
Section: Empathy and Leadershipmentioning
confidence: 99%
“…In general, very little is known about the overuse of empathy, but research by Zloteanu, Bull, and Richardson (2019) suggested that one possible downside of very high empathy in leaders is the possible misinterpretation of deceptive emotional cues in others (but not genuine expressions of affect). Although warmth and empathy typically generate positive social relations with others, excessive empathy can sometimes cause others to feel pressured to react with similar enthusiasm (Hu, Zhang, Jiang, & Chen, 2019).…”
Section: Developing Empathy In Individuals and Organizationsmentioning
confidence: 99%
“…Accordingly, people may be motivated to feign emotional facial expressions to evoke a desired response from others ( DePaulo, 1992 ; Goffman, 1959 ). These attempts at manipulation are thought to be highly successful; research consistently finds that explicit lie detection accuracy is at or near chance ( Bond & DePaulo, 2006 ), and that observers perform similarly poorly in discriminating genuine versus deceptive expressions of emotion ( Ekman & O’Sullivan, 1991 ; Hess & Kleck, 1994 ; Porter & ten Brinke, 2008 ; Stel & van Dijk, 2018 ; Zloteanu, 2019 ). Here, we bring together the social functional account of emotions ( Keltner & Gross, 1999 ; Van Kleef, 2009 ) and findings on behavioral cues to deceptive emotional expressions ( Ekman, 2003 ; Ekman et al, 1988 ; Frank et al, 1993 ; Hill & Craig, 2002 ; Hurley & Frank, 2011 ; Porter et al, 2012 ; Porter & ten Brinke, 2008 ; ten Brinke et al, 2012 ; ten Brinke & Porter, 2012 ) to suggest that—despite poor explicit accuracy—observers will experience different emotional and behavioral reactions to genuine versus deceptive displays of sadness, indicating sensitivity to subtle cues of deception on the face.…”
mentioning
confidence: 99%